ROLES OF TRANSFORMING GROWTH FACTOR BETA AND INTERLEUKIN-32 IN CYSTIC ECHINOCOCCOSIS - Saad, Riyadh Resan; Khalaf, Maysara Samer; Atiyah, Amal Hasan (Eastern Ukrainian Medical Journal, 2025)
Introduction. The biologically different subspecific strain Echinococcus granulosus may infect domestic animals and people to varying degrees. Cystic echinococcosis (CE) is a severe zoonotic parasite that poses a significant threat to humans and animals. Epidemic echinococcosis diseases threaten people and animals, slow animal husbandry, and hurt the economy. This study evaluated the significance of immunological markers, including transforming growth factor beta (TGF-β) and interleukin-32 (IL-32), in CE. Methods. Fifty CE patients and 50 healthy controls were recruited for the study. Blood samples were collected from all participants to determine their serum TGF-β and IL-32 levels using the enzyme-linked immunosorbent assay (ELISA) technique. Results. The demographics of the study groups showed that most patients infected with CE were males (78.0%) within the age group 16–25 (30.0%), most had cysts in the liver (58.0%) with the fertile type (74.0%), and finally, most lived in rural areas (82.0%). There was a significant (p ≤ 0.0001) increase in the levels of TGF-β and IL-32 in patients (17.82±7.34 and 21.70±7.12 pg/mL, respectively) compared with the controls (5.13±1.45 and 3.12±1.69 pg/mL, respectively). No significant differences (p > 0.05) between the levels of TGF-β and IL-32 were observed based on the site of Echinococcus granulosus cysts, type of cysts among patients, and residence of patients. Conclusion. The liver had more hydatidosis than the lung. The study’s findings revealed that the Echinococcus granulosus cyst site, kind, and residence did not significantly impact TGF-β and IL-32 levels in patients.